Electrophysiological evidence for an attentional bias in processing body stimuli in bulimia nervosa - Mai, Sandra; Friederich, Hans-Christoph (Biological psychology, 2015)
Empirical evidence suggests abnormalities in the processing of body stimuli in bulimia nervosa (BN). This study investigated central markers of processing body stimuli by means of event-related potentials in BN. EEG was recorded from 20 women with BN and 20 matched healthy controls while watching and evaluating underweight, normal and overweight female body pictures. Bulimics evaluated underweight bodies as less unpleasant and overweight bodies as bigger and more arousing. A higher P2 to overweight stimuli occurred in BN only. In contrast to controls, no N2 increase to underweight bodies was observed in BN. P3 was modulated by stimulus category only in healthy controls; late slow waves to underweight bodies were more pronounced in both groups. P2 amplitudes to overweight stimuli were correlated with drive for thinness and body dissatisfaction. We present novel support for altered perceptual and cognitive-affective processing of body images in BN on the subjective and electrophysiological level.
Gesehen am 24.08.2017